Comparison of HCA and SHO/IMP Control Methodologies for Tip Damping of the Commercial Piezoelectric Transducer - (:unkn) unknown (DESTECH PUBLICATIONS, INC, 2017)
This study investigates and compares Harmonic Control Array (HCA) and Simple Harmonic Oscillator (SHO), or namely Internal Modal Principle (IMP), methodologies for tip damping of the commercial piezoelectric transducer (Mide, Volture PPA-1011) via voltage control under two conditions: (1) Tip displacement at different amplitudes (input) without base vibration input (no disturbance) and (2) by exact opposite of the fist condition; in the presence of base vibration at resonance frequency of the transducer with zero initial condition for tip displacement. Results indicated that HCA is capable to damp both cases and for the first case, with proportional controller alone and for the latter case, via proportional-integral (PI) controller regarding voltage boundary condition at different input and disturbance amplitudes, whereas SHO is unable to control the damping of the transducer tip for the first condition. Alternatively, for the second case, SHO damps remarkably faster than HCA. As an advantage, for both HCA and SHO, optimum gain constants for each case remain unchanged as the amplitude of initial conditions and disturbance vary.
Keywords: Harmonic Control Array (HCA); Simple Harmonic Oscilator (SHO); Internal Modal Principle (IMP); Piezo damping; Piezoelectric transducer damping; Vibration control; Harmonic assembler; Harmonic disperser; Periodic control